A Study on the Relative Response of 3 Cassava Varieties to Chemical Fertilizers and Weeding Methods - Piya Duangpatra (Agriculture and Natural Resources, 1990)
Field experiment was carried out on sandy soil classified as Sattahip soil series during June 1988 through June 1989 at Sriracha Research Station, Chon Buri province. The main objective was to assess the relative response of 3 cassava varieties : Rayong 1, Rayong 60 and MKUC 27-3-23 to 3 rate of mixed fertilizer grade 15-15-15 : 0, 100 and 200 kg/rai and two weeding methods : chemical treatment (diuron + alarchlor ) and handweeding. The experimental design was a split-split plot with 3 replications each of which having cassava varieties, weeding methods and mixed fertilizer rates as the main plot, sub-plot and sub –sub –plot respectively. Weeding by chemical treatment and handweeded were used at planting time and at 30 days after planting respectively. All fertilizer materials were applied locally to each plant at 30 days after planting. During the course of plant growth through maturity at 12 month old, measurements were made on 1) cutting germination at 40 day after planting 2) fresh weight of plant above ground at maturity and 3) fresh and dry weights of root at maturity. Additionally, some cost analyses were made by determining the VCR (value to cost ratio ) values to estimate the economic return pertinent particularly to the relative response to mixer fertilizer rates of 3 cassava varieties. At 40 days after planting, the percent of cutting germination of cassava varieties Rayong 60 and MKUC 27-3-23 were fairly high whereas that of the Rayong 1 was the lowest. For weeding treatment, both methods: application of Diuron + Alacholr and handweeding were equally effect in controlling weeds. The herbicidal spray exerted insignificant impacts on cutting germination fresh weight of plant top as well as fresh and dry root weights. Regardless of mixed fertilizer rates cassava varieties MKUC 27-3-23 gave higher fresh and dry weights of root than those of the Rayong 1 and Rayong 60. By average, the highest response to rates of mixed fertilizer grade 15-15-15 was obtained at 100 kg/rai. At this fertilizer level, the magnitude response of cassava varieties Rayong 1 and Rayong 60 were higher than that of MKUC 27-3-23. Nevertheless, under this unfertilized poor soil ; cassava variety MKUC 27-3-23 substantially outyielded Rayong 1 and Rayong 60. By estimating the economic return base on VCR ( value to cost ratio ) values, it was noted that cassava variety MKUC 27-3-23 gave the highest return in term of cassava chip price. Regardless of cassava varieties, the highest economic return was attained at 100 kg.rai of mixed fertilizer grade 15-15-15 . Base on the overall results of this experiment, the obvious merits of cassava variety MKUC 27-3-23 are as follows : 1) good germination 2) give acceptable root yield even in unfertilized poor fertile soil 3) tend to produce rather high root yield at low level of fertilizer application in poor fertile soil and 4) gave fairly high and higher economic return than cassava variety Rayong 1 and Rayong 60 at least under this or very resemble to this experimental materials and environments particularly soil type and climatic conditions.